ANALISIS PENGARUH KEMAMPUAN KERJA DAN KOMPENSASI TERHADAP KINERJA DENGAN MOTIVASI KERJA SEBAGAI VARIABEL MODERATING PADA APARATUR SIPIL NEGARA DINAS PARIWISATA KABUPATEN PONOROGO - Pudihastuti, Fitri; Wahyudi, Amin; Sriwidodo, Untung (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
The population used in this study were 45 Civil Servants at Ponorogo Regency Tourism office. Data collection techniques used a questionnaire that has passed the test of validity and reliability. The regression requirements test used the classic assumption test. Data analysis techniques used multiple linear regression analysis with absolute difference test and hypothesis testing is done through t test. The results of this study indicate that: (1) Work ability significantly influences the performance of Civil Servants at Ponorogo Regency Tourism office. This is evidenced from the calculation of the t test which produces a probability value (0,000) < 0.05. Thus this hypothesis is proven true. (2) Compensation has no significant effect on the performance of Civil Servants at Ponorogo Regency Tourism office. This is evidenced from the calculation of t test that produces a probability value (0,603)> 0,05. Thus this hypothesis is proven true. (3) Work motivation has a significant effect on the performance of Civil Servants at Ponorogo Regency Tourism office. This is evidenced from the calculation of the value of t test which results in a probability value (0,000) < 0,05. Thus this hypothesis is proven true. (4) Work motivation does not moderate the effect of work ability on performance on Civil Servants at Ponorogo Regency Tourism office. This is evidenced from the calculation of the absolute difference value 1 test which produces a probability value (0,437) > 0,05. Thus this hypothesis is proven true. (5) Work motivation does not moderate the effect of compensation on performance on Civil Servants at Ponorogo Regency Tourism office. This is proven by the results of compensation regression analysis that does not significantly influence the performance of the State Civil Service of the Tourism Agency of Ponorogo Regency. Thus to improve the performance of the State Civil Service Agency of the Tourism Office of Ponorogo Regency is not supported by compensation, although work motivation has a significant effect on the performance of the State Civil Service of the Tourism Office of the Regency of Ponorogo